How did covid19 affect online postgraduate students? A case study - Rosas Mendoza, Alejandro M.; Molina Zavaleta, Juan Gabriel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
We present 2 cases of active mathematics teachers, meanwhile study in an online and asynchronous master’s program in Educational Mathematics, and the complications they experienced with the closure of the schools where they teach due to the COVID-19 pandemic. The shift from face-to-face classes to online classes required them to learn new tools and develop new skills, forcing them to spend more time preparing for their classes and less time on their master’s studies. The result was that instead of graduating in 4 or 5 semesters, students took 6 or 7 semesters to complete their research and write their thesis.